Analysis of User Acceptance of The 2013 Curriculum E-Report from a Gender Perspective using UTAUT Model - Megawati Megawati; Rimet Rimet; Tita Alisya (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
SMK IT Al-Izhar Pekanbaru has implemented an Information System for Managing Report Values to make it easier for teachers to manage student report cards. This report card system has been used since 2015. The behavioral aspect is a very important aspect, because it relates directly to users. The thing that underlies this research is that there are still teachers who do not understand how to input student grades, so they tell other teachers to input grades into the system. The purpose of this study was to determine the factors that most influence user behavior interest based on the UTAUT variable consisting of performance expectancy, effort expectancy, social influence, facilitating conditions and moderated by gender, age and experience variables. The results of this study indicate that the factors that most influence user behavior interest are performance expectancy, effort expectancy, and facilitating conditions. while the moderator variable gender affects user interest by 79.0%. As well as the finding of a gap (GAP) between the expectations of the school and the perception of users. To overcome the GAP, the school must evaluate and monitor the implementation of the report card value management information system at SMK IT Al-Izhar Pekanbaru.